Multi-order optical spatial vortex filters for simultaneous contour extraction of various parts of an object - S.N. Khonina; A.P. Porfirev; P.A. Khorin; A.P. Dzyuba; D.P. Serafimovich; R.V. Skidanov (Компьютерная оптика)
We study the transformation of the analyzed object by a variety of spatial filters including bandpass, differential, radial filters, various types of vortex filters, and Hilbert filters. Advantages and disadvantages of different filters in terms of clarity and direction-invariance of edge extraction, as well as the energy efficiency are numerically demonstrated. Based on the results obtained, multi-order optical spatial vortex filters with different parameters are developed for simultaneously extracting contours of various object parts. We show that a multi-order filter makes it possible to form a set of images in one plane with a clearly defined contour, object corners and various parts of the contour. Numerical and experimental testing of 4- and 5-channel spatial vortex filters of various types was applied for test objects. A possibility of using the proposed filters to simultaneously highlight the edges of the entire image and various parts of the image in order to extract more features from the analyzed image is shown.